Combining ability and heterosis for fruit yield and quality in manzano hot pepper (Capsicum pubescens R P) landraces - Perez Grajales, M.=700 1 Gonzalez Hernandez, V.A.; Peña Lomeli, A.; Sahagum Castellanos, J.
(ES, En)
Ilus., 20 ref.
Keywords: CAPSICUM PUBESCENS; FITOMEJORAMIENTO; VIGOR HIBRIDO; MEXICO; CHILE MANZANO; REVISTA CHAPINGO: SERIE HORTICULTURA